Omalizumab Use in Chronic Spontaneous Urticaria during Pregnancy and a Four Years’ Follow-Up: A Case Report - Laura Michelina Losappio (Case Reports in Dermatology, 2020)
Chronic spontaneous urticaria (CSU) is a benign skin disorder usually responsive to treatment; however, at times it can be difficult to control and become very debilitating. We discuss the case of a woman with CSU that was unresponsive to H1-antihistamines who was treated with omalizumab and became pregnant during omalizumab treatment. We also considered the follow-up of the mother and newborn for 4 years after delivery. Our case report confirms that omalizumab is a safe and effective therapeutic option, after careful evaluations in terms of cost-effectiveness, in pregnant and lactating women with severe chronic urticaria. Assessment throughout follow-up confirmed a regular progression of pregnancy parameters and no adverse reaction was documented in the child from birth to 4 years of age.